The Influence of Salary Compensation, Leadership Communication, Work Culture, Competence, and Motivation on The Work Productivity of Generation Z In Culinary MSMES In Balikpapan - Ferinda, Yosica; Krisprimandoyo, Denpharanto Agung; Christiani, Natalia (Publikasi Indonesia, 2025)
This study analyzes the effect of salary compensation, leadership communication, work culture, competence, and motivation on the work productivity of Generation Z in culinary MSMEs in Balikpapan, using multiple linear regression with 135 respondents. The study reveals that Generation Z is a workforce group with unique characteristics that require an adaptive and innovative management approach. The results show that competence has a positive and significant effect (B=0.348; p<0.05), while salary compensation (B=-0.117; p<0.05) and leadership communication (B=-0.242; p<0.05) have significant negative effects. Work culture and motivation are not significant partially, but simultaneously, all variables have a significant effect. These findings provide practical recommendations for MSMEs to optimize competency development, revise compensation schemes, and improve leadership communication to suit the characteristics of Gen Z.